Penyelesaian Permohonan Pailit Melalui Instrumen Insolvency Test Sebagai Perlindungan Hukum Bagi Pihak Terkait Dalam Kepailitan - Muhammad Dito Zakharia; Ahmad Syaifudin; Benny Krestian Heriawanto (Unram Law Review, 2025)
Indonesian law has undergone several revisions. Still, with the various revisions, according to the author, it has not provided maximum legal protection and legal certainty to the parties involve in bankruptcy law itself, on the other hand, the Indonesian bankruptcy law regulation is more likely to favor the interests of creditors, can prove this that the bankruptcy law regulation in Indonesia does not require a minimum amount of receivables and does not regulate insolvency requirements. Regarding the lack of regulation of insolvency requirements in bankruptcy applications, this harms debtors who are still solvent as they can be filed for bankruptcy. There is a need for an insolvency test to determine whether the debtor is solvent or insolvent. With the implementation of the insolvency test the bankruptcy legal regime is appropriate because, under it only debtors who are genuinely unable to pay debts can be terminated by bankruptcy given the principle of insolvency. Therefore, implementing the insolvency test in bankruptcy law in Indonesian will provide legal certainty for debtors and protection to solvent debtors. In conducting this legal research, a normative juridical methodology was employed, drawing on statutory conceptual, and comparative approaches.